Kāndūlǣ phūsūngʻāyu : khwāmsuk læ khwāmkhlīat = caregiving to older persons : happiness and stress - Rotsarin Krē (ʻĒkkasān thāng wichākān/Sathāban Wičhai Prachākō̜n læ Sangkhom, Mahāwitthayālai Mahidon, 2013)
On health care and quality of life of the older people in Thailand in terms of stress.